The rise of crowdfunding in the cultural field. A new architecture for shared production or simply a reformulation of fragility and precariousness? - Nicolás Barbieri; Xavier Fina; Adriana Partal; Joan Subirats (Arbor: Ciencia, Pensamiento y Cultura, 2019)
Crowdfunding experiences, especially in the cultural field, have expanded in an unthinkable manner in the last few years. This phenomenon is linked to the major transformation of the Internet in many aspects of social, economic and political activity. Together with private and commercial production, new spaces for production and social exchange have been created. However, it is crucial to verify the degree to which these new spaces of technical and economic feasibility find the right results in social return and its practices. Does the rise in crowdfunding in the cultural field represent a new-shared production or is it merely a fragile and precarious reformulation of the sector? By analysing the activities of several crowdfunding platforms this article answers these questions and proposes four dimensions to study the social return and public value of crowdfunding. We conclude that crowdfunding not only incorporates innovation to the well-established intermediary dynamics of the cultural sector, but can also reproduce the institutional rules and status quo.